Pedagogic Competency Profile: A Review of Learning Transformation as Learning Conditioning on Student Portfolio Ability - Ratnawati Susanto; Yuliati Yuliati; Yulhendri Yulhendri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The condition and situation of education after the Covid 19 Pandemic caused